(untitled) - Syers, J.K; Food and Agriculture Organization of the United Nations (Rome, 2008)
This report has benefited from the valuable inputs provided at all stages of its preparation by the other joint sponsors: the fercilizer Institute, the International Fertilizer Industry Association, the International Plant Nutrition Institute, and the World Phosphate Institute.
Keywords: Phosphatic fertilizers,Soils,Phân lân,Đất; Phosphorus content,Lượng phân lân